Chinese management practices in Kenya: toward a post-colonial critique - Kamoche, Ken; Siebers, Lisa Qixun (Taylor and Francis, 2015)
While transforming the investment, trading and infrastructural landscape in Africa, Chinese firms are also generating much-publicised controversy about their real motives. Many of the large Chinese firms operating in Africa focus mostly but not exclusively on engineering, infrastructural projects and mining. This Africa–China engagement has only recently begun to receive critical attention in the area of management and organisation studies. With reference to Kenya, we found that this phenomenon is characterised by four key themes: the unique yet diverse motivations of investors, the challenge of reconciling cross-cultural differences, the impact of low-cost strategies and the boundary-spanning role of managers. This paper also considers the extent to which post-colonial theory might serve as an analytical lens for examining the perceptions and attitudes of Chinese managers as well as the experiences of the Africans who work for them.